Suicide attempt survivors’ recovery-related agency in the relational context of services: a qualitative analysis - Selma Gaily-Luoma; Jukka Valkonen; Juha Holma; Aarno Laitila (BMC Public Health)
Abstract Background Suicidal persons’ contacts with services present a key opportunity for suicide prevention. However, interventions by services are not always effective. A deeper understanding of suicidal service users’ agency and its implications may facilitate the provision of meaningful responses to help-seeking during suicidal crises. This abductive study explores the recovery-related agency of suicide attempt survivors and the perceived role of interactions with services in facilitating or hindering it. Methods Fourteen Finnish suicide attempt survivors were interviewed in-depth on their experiences of interacting with services during a recent suicidal episode. An operationalization of recovery-related agency as the expressed ability to take (mental or physical) action in a direction perceived as aiding recovery from suicidality (i.e., the coupling of recovery-related intentionality and power) was used to explore transcribed interviews through directed content analysis. Data were further categorized based on whether the service context was perceived as helpful or unhelpful to recovery efforts. Results All participants expressed both agency and non-agency in relation to their recovery process. The relational context provided by services was presented as highly relevant for the achievement and sustainability of recovery-related agency as well as for participants’ experience of safety in instances when agency was lacking. The results are presented as a typology of recovery-related agency in its perceived relational context, with the categories of sustained agency, strained agency, contained non-agency and uncontained non-agency. Conclusions The concept of agency helped capture important aspects of suicidal individuals’ recovery-related efforts and the role of services in facilitating or hindering them. The findings illuminate the value of viewing suicidal service users as agents of their own recovery process as well as the potential costs of ignoring this perspective in service delivery and design.